Textiles and clothing sustainability : sustainable fashion and consumption - Muthu, Subramanian Senthilkannan (Textile science and clothing technology., 2016)
This is the first book to introduce and explain the concept of sustainable consumption with reference to the clothing sector. It uses various case studies to detail sustainable consumption behavior in the industry. Consumption is a key issue and is a major driver when it comes to sustainability in any industry, including clothing sector. Several studies which have highlighted the need for sustainable consumption in the clothing sector are discussed in this book.